(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article explores a methodology for developing students’ technological thinking based on the ART design (Art, Research, Technology) approach in the context of digital education. The study examines issues related to enhancing students’ creativity and problem-solving thinking through the use of modern pedagogical technologies, design thinking, and digital tools.